Implikasi Manajemen Pendidikan Islam dalam Kerangka Kebijakan Pengembangan Ilmu Pengetahuan Nasional: Perspektif Institusi DPR - Reza Fachlevi, Ahmed; Eka Wardhana, Kautsar; Binti Kholifah, Yusnia (Economic Reviews Journal, 2025)
This article examines the correlation between knowledge, science, and religion within the context of public service at the East Kalimantan Regional House of Representatives (DPRD). The integration of these three elements is essential since public service must not only be efficient and rational, as emphasized by scientific principles, but also grounded in moral and religious ethics. This research employs a descriptive qualitative approach through literature review and policy document analysis of DPRD East Kalimantan. The findings indicate that knowledge and science strengthen the rationality of public policies, while religion provides the moral and ethical foundation for public accountability. The correlation among the three creates a holistic governance model that promotes professionalism and integrity. In conclusion, the harmony of knowledge, science, and religion forms the basis for improving public service quality rooted in intellectual and spiritual values within DPRD East Kalimantan.